2018
DOI: 10.3390/nu10010093
|View full text |Cite
|
Sign up to set email alerts
|

Interstitial Glucose and Physical Exercise in Type 1 Diabetes: Integrative Physiology, Technology, and the Gap In-Between

Abstract: Continuous and flash glucose monitoring systems measure interstitial fluid glucose concentrations within a body compartment that is dramatically altered by posture and is responsive to the physiological and metabolic changes that enable exercise performance in individuals with type 1 diabetes. Body fluid redistribution within the interstitial compartment, alterations in interstitial fluid volume, changes in rate and direction of fluid flow between the vasculature, interstitium and lymphatics, as well as altera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
48
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 50 publications
(51 citation statements)
references
References 78 publications
(116 reference statements)
1
48
1
1
Order By: Relevance
“…One might assume that physical exercise per se did not deteriorate the performance of the flash GM system, because the rate of change in glucose appeared to result in inaccuracy. In the present study, the MARD during exercise was inherently higher than that with other CGM devices such as Minimed 640G (Medtronic), Dexcom G4 Platinum (Dexcom) or Paradigm Veo Enlite (Medtronic) (mean absolute relative difference/MARD, ~18%) . A systematic overestimation of 2.7 mmol/L might suggest that anticipation of intervention to avoid exercise‐induced hypoglycaemia is required as soon as an interstitial glucose level of 7.2 mmol/L is reached.…”
Section: Discussionmentioning
confidence: 52%
See 2 more Smart Citations
“…One might assume that physical exercise per se did not deteriorate the performance of the flash GM system, because the rate of change in glucose appeared to result in inaccuracy. In the present study, the MARD during exercise was inherently higher than that with other CGM devices such as Minimed 640G (Medtronic), Dexcom G4 Platinum (Dexcom) or Paradigm Veo Enlite (Medtronic) (mean absolute relative difference/MARD, ~18%) . A systematic overestimation of 2.7 mmol/L might suggest that anticipation of intervention to avoid exercise‐induced hypoglycaemia is required as soon as an interstitial glucose level of 7.2 mmol/L is reached.…”
Section: Discussionmentioning
confidence: 52%
“…Although the flash GM system demonstrated good efficacy in chronic glucose monitoring settings, the accuracy of acute continuous glucose monitoring (CGM) systems was impaired during periods of high rates of change in glucose . From a physiological point of view, a time lag was observed in the interval needed for glucose to diffuse from the bloodstream into the interstitium .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To overcome this lag time and to reduce the risk of inadequate therapy decisions, an exercise-related algorithm could improve sensor performance [10]; however, a recent study in people with Type 1 diabetes receiving continuous subcutaneous insulin infusion showed that a 50% reduction in basal rate 1 h before the start of exercise testing did not significantly reduce free circulating insulin during exercise [11]. To overcome this lag time and to reduce the risk of inadequate therapy decisions, an exercise-related algorithm could improve sensor performance [10]; however, a recent study in people with Type 1 diabetes receiving continuous subcutaneous insulin infusion showed that a 50% reduction in basal rate 1 h before the start of exercise testing did not significantly reduce free circulating insulin during exercise [11].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, despite it having being shown that blood glucose collected from the earlobe in comparison to the fingertip does not result in clinically relevant differences under resting conditions [13], a sampling-site bias might be present, especially in exercise conditions [14]. Additionally, despite it having being shown that blood glucose collected from the earlobe in comparison to the fingertip does not result in clinically relevant differences under resting conditions [13], a sampling-site bias might be present, especially in exercise conditions [14].…”
Section: Discussionmentioning
confidence: 99%